A Study of a Caucasian Family with Variant von Willebrand’s Disease in Association with Vascular Telangiectasia and Haemoglobinopathy - Hanna, W; McCarroll, D; Lin, D; Chua, W; McDonald, T P; Chen, J; Congdon, C; Lange, R D (Thrombosis and Haemostasis, 1984)
A family was identified which carries multi-haematological disorders including Type IIA von Willebrand’s disease, vascular telangiectasia, and a haemoglobinopathy (haemoglobin S trait). In the affected individuals, the von Willebrand’s disease varies in its expression from an asymptomatic form to a severe form especially in those patients with telangiectasia. Some patients have vascular telangiectasia in the mucous membranes of the mouth and lips. In two patients endoscopy disclosed telangiectasia in the mucous membranes of the gastrointestinal tract. All of the patients who had telangiectasia also had von Willebrand’s disease. An incidental finding was the presence of an abnormal haemoglobin (haemoglobin S) in some family members. The pattern of inheritance of the haemoglobinopathy was unrelated to the inheritance pattern of von Willebrand’s disease. The presence of haemoglobin S did not interfere with the aggregation of platelets in response to ristocetin.
Keywords: Variant II A von Willebrand’s disease; Haemoglobinopathy; Vascular telangiectasia